Z badań nad działalnością teatru obozowego w Arswalde 1940–1941 i Woldenbergu 1941–1945 - Boruń-Stelmaszczyk, Anna (Acta Universitatis Lodziensis. Folia Historica, 1984)
This article describes a fragment of studies on activities of camp theatres at Arswald and Woldenberg between 1940–1945. It starts with a short characteristic of the repertoire, founders of the theatres, actors, and audience. The camp theatre was established and run exclusively by prisoners of war, and it had a definite soldier-audience. This exerted an influence on its repertoire and determined its function among the camp community. The analysis encompasses the texts of Stefan Flukowski (1902–1972) written at Arswald and Woldenberg in the years 1940–1945 for the local theatrical stage. In these works of special interest is application of the symbol by the author. The symbol was holding a specific place in the creative work of camp theatres. There were introduced these symbols on the stage the materialization of which included the contents being most valid for the camp community. These were national symbols: Wawel Castle, King Sisigmund's Bell, knights' ensigns so valuable for a soldier-prisoner as well as symbols linked with the camp life and the personal situation of prisoners. The problems of captivity and confinement on a relatively small area of several thousand men were of the utmost significance here. This fact caused that some subjects became an obsession with prisoners e.g. problem of love, woman, longing, need of fulfilment as a man or of finding confirmation for oneself. The theatre moving all the se problems on the stage was performing a cathartic function in relation to spectators. It was the only place where a spectator was getting involved in these emotions and this experience, which he could not express or respond to otherwise because of the censorship and specifics of the camp community. It was purifying the psyche of spectators, raising their spirits, and giving a hope for survival.